Sphingomonas paucimobilis an unusual cause of subdural empyema in pediatric: a case report - Annisa Muhyi; Amalia Aswin (Medical Faculty of Brawijaya University, Indonesia, 2022)
Introduction: Acute bacterial meningitis continues to be a neurological emergency with high mortality and morbidity Case: We report the case of a pediatric patient with subdural empyema due to Sphingomonas paucimobilis. A 2-month-old infant developed fever, generalized seizures, and worsening general status. He had a cough for two weeks, and a chest X-ray showed pneumonia. Laboratory tests reveal marked leukocytosis, a white blood cell count of 28.500/mL, and an elevated platelet level of 654.000 mg/dL. A computerized brain tomography revealed an empyema subdural. A cerebrospinal fluid analysis showed unclear fluid, revealed cell count 3560 cells, 90% mononuclear and 10% polymorphonuclear, red blood cell count of 0/mm3, protein of 370 mg/dL, and glucose of 35 mg/dL. His cerebrospinal fluid culture showed Sphingomonas paucimobilis sensitive to cephalosporin, levofloxacin, meropenem, imipenem, gentamycin, tobramycin and amikacin. He was treated empirically with meropenem. The patient had a rapid recovery from the seventh day of treatment and was discharged on hospital day 14. Conclusion: We highly recommend raising awareness about subdural empyema as a complication for acute bacterial meningitis caused by S. paucimobilis in community-acquired infection.